2014
DOI: 10.1007/s00253-014-6169-6
|View full text |Cite
|
Sign up to set email alerts
|

Microbial biofilms: biosurfactants as antibiofilm agents

Abstract: Current microbial inhibition strategies based on planktonic bacterial physiology have been known to have limited efficacy on the growth of biofilm communities. This problem can be exacerbated by the emergence of increasingly resistant clinical strains. All aspects of biofilm measurement, monitoring, dispersal, control, and inhibition are becoming issues of increasing importance. Biosurfactants have merited renewed interest in both clinical and hygienic sectors due to their potential to disperse microbial biofi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
114
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(119 citation statements)
references
References 97 publications
1
114
0
4
Order By: Relevance
“…The agr regulatory system controls a myriad of secreted toxins and enzymes, and identifying the exact agents responsible for dispersal has represented a challenge. Early studies suggested that surfactant properties of ␦-toxin could be responsible (69), considering that many bacterially produced surfactants have known anti-biofilm effects (77). As it became evident that ␦-toxin was part of a larger family of PSM peptides (78), further studies demonstrated that multiple PSMs are important in modulating S. aureus biofilm structure (79).…”
Section: Quorum Sensing and Biofilm Interconnectionsmentioning
confidence: 99%
“…The agr regulatory system controls a myriad of secreted toxins and enzymes, and identifying the exact agents responsible for dispersal has represented a challenge. Early studies suggested that surfactant properties of ␦-toxin could be responsible (69), considering that many bacterially produced surfactants have known anti-biofilm effects (77). As it became evident that ␦-toxin was part of a larger family of PSM peptides (78), further studies demonstrated that multiple PSMs are important in modulating S. aureus biofilm structure (79).…”
Section: Quorum Sensing and Biofilm Interconnectionsmentioning
confidence: 99%
“…The surface and interfacial tension reducing properties of surfactants provide excellent detergency, emulsification, foaming and dispersing traits, making them some of the most versatile products in chemical processes [22]. The current hypothesis is that surface-active molecules like biosurfactants play a major role in the development and maintenance of biofilms, partly through the maintenance of water channels through the biofilm which enhance nutrient movement and gaseous exchange which leads to the dissociation of parts of the biofilm into planktonic mobile forms [5]. Several strands of research have demonstrated that under certain testing conditions, biosurfactants can be more effective than many traditional biofilm inhibition and or disruption strategies [23].…”
Section: Discusionmentioning
confidence: 99%
“…Biosurfactants have long been reported as molecules with potential applications in environmental and biomedical related areas [5,6,7]. There is renewed interest mounting in the use of biosurfactants in healthcare associated infections [8] and in particular the rapid advances in biofilm inhibition, control or disruption involving their use.…”
Section: Introductionmentioning
confidence: 99%
“…Biosurfactants are another promising class of substances with possible implementations on the treatment of biofilm-related infections. In a recent review, Banat et al (74) highlighted some properties of biosurfactants towards clearance or prevention of biofilms, including inhibition of initial adherence and disruption of biofilm structure, in a range of bacterial and fungal strains. Synergistic inhibition effect with conventional antimicrobials has also been described (75).…”
Section: Compounds and Enzymes To Disperse Or Dissolve Biofilmsmentioning
confidence: 99%
“…van Tilburg Bernardes et al Page 6 Biological surface-active agents, also known as biosurfactants, are a heterologous and versatile class of chemicals with amphiphilic properties, produced by microorganisms (74). Biosurfactants are another promising class of substances with possible implementations on the treatment of biofilm-related infections.…”
Section: Compounds and Enzymes To Disperse Or Dissolve Biofilmsmentioning
confidence: 99%